2003
DOI: 10.1002/jbm.a.10582
|View full text |Cite
|
Sign up to set email alerts
|

Performance of degradable composite bone repair products made via three‐dimensional fabrication techniques

Abstract: This study analyzed the in vivo performance of composite degradable bone repair products fabricated using the TheriForm process, a solid freeform fabrication (SFF) technique, in a rabbit calvarial defect model at 8 weeks. Scaffolds were composed of polylactic-co-glycolic acid (PLGA) polymer with 20% w/w beta-tricalcium phosphate (beta-TCP) ceramic with engineered macroscopic channels, a controlled porosity gradient, and a controlled pore size for promotion of new bone ingrowth. Scaffolds with engineered macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(150 citation statements)
references
References 38 publications
4
139
0
1
Order By: Relevance
“…High levels of interconnectivity between the pores enhance the porosity and enlarge the superficial area and consequently increase the numbers of endothelial cells and active osteoblasts. 35,36 It is important to note that our histological evidence revealed obvious cell migration from the peripheries to the cores of the nHA/coral blocks at the 3-week time point; collagen matrices were also readily observable in the centers. There were more newly formed blood vessels and greater quantities of bone tissue present at the 8-week time point.…”
mentioning
confidence: 79%
“…High levels of interconnectivity between the pores enhance the porosity and enlarge the superficial area and consequently increase the numbers of endothelial cells and active osteoblasts. 35,36 It is important to note that our histological evidence revealed obvious cell migration from the peripheries to the cores of the nHA/coral blocks at the 3-week time point; collagen matrices were also readily observable in the centers. There were more newly formed blood vessels and greater quantities of bone tissue present at the 8-week time point.…”
mentioning
confidence: 79%
“…Roy et al found that in a PLGA/b-TCP composite scaffold with a porosity gradient from 80% to 88%, bone tissue formation was enhanced in the region with higher porosity after implantation in rabbit craniums. 123 Kruyt et al also demonstrated higher proliferation of goat bone marrow stromal cells in hydroxyapatite scaffolds with 70% porosity and an average pore size of 800 mm compared to those with 60% porosity and an average pore size of 700 mm during a 6-day ex vivo culture. 124 However, in vitro osteogenesis has been shown to increase with lower porosity.…”
Section: -102mentioning
confidence: 94%
“…7,8 The pore interconnectivity allows for cell ingrowth, vascularization, and nutrient diffusion for cell survival. [9][10][11] The extent of ECM secretion also increases by increasing the pore size. 8 It was found that in genipin crosslinked gelatin hydrogels with smaller pores, the tendency was tilted toward cell growth rather than of ECM secretion, 8 resulting in overconfluence during the middle and late stages of differentiation; consequently, the extent of ECM secretion decreased compared to that within gelatin hydrogels with larger pores.…”
mentioning
confidence: 99%